Female sex workers in Kigali, Rwanda: a key population at risk of HIV, sexually transmitted infections, and unplanned pregnancy. (May 2019) - Ingabire, Rosine; Parker, Rachel; Nyombayire, Julien; Ko, Jasmine E; Mukamuyango, Jeannine; Bizimana, Jean; Price, Matt A; Laufer, Dagna; Tichacek, Amanda; Wall, Kristin; Allen, Susan; Karita, Etienne
Female sex workers (FSWs) were recruited from known hotspots in Kigali, Rwanda, and offered free, anonymous human immunodeficiency virus (HIV) counseling and testing, diagnosis and treatment of sexually transmitted infections (STIs) and long-acting reversible contraception (LARC). From September 2012 to March 2015, 1168 FSWs sought services, including 587 (50%) who were HIV-positive. More than 90% had previously tested for HIV, and 26% who reported previously testing negative had seroconverted. Of the 349 who already knew their HIV-positive status, 74% were on antiretroviral treatment. The prevalence of serologic syphilis was 43% in HIV-positive and 19% in HIV-negative FSWs (p < 0.0001), and Trichomonas vaginalis was found in vaginal wet mounts in 21% of HIV-positive and 13% of HIV-negative FSWs (p < 0.0001). Signs and symptoms of STIs were found in 35% of HIV-positive compared with 21% of HIV-negative FSWs (p < 0.0001). Only one-third reported consistent condom use in the last month. Modern contraceptive use was reported by 43% of HIV-positive and 56% of HIV-negative FSWs (p < 0.0001). Current pregnancy was reported by 4% of HIV-positive and 6% of HIV-negative FSWs (p = 0.0409). Despite Rwanda's successes with preventing 70% of new infections in the general population through nationwide couples' testing in antenatal clinics, prevention and timely treatment in key populations including FSWs are lacking. The prevalence of HIV – including many new cases – and STIs among FSWs in Kigali is high and condom and contraceptive use are low. Tailored and integrated HIV/STIs and family planning programs are urgently needed for FSWs.